If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-36=-4(c+72)
We move all terms to the left:
-36-(-4(c+72))=0
We calculate terms in parentheses: -(-4(c+72)), so:We get rid of parentheses
-4(c+72)
We multiply parentheses
-4c-288
Back to the equation:
-(-4c-288)
4c+288-36=0
We add all the numbers together, and all the variables
4c+252=0
We move all terms containing c to the left, all other terms to the right
4c=-252
c=-252/4
c=-63
| a3=10 | | 190=4b^2- | | 30+2t=4t | | 44g-5=0 | | 2x+3x-6=3x+2x-7+1 | | d+17/8=4 | | 4=(7a) | | 27/30=n/40 | | h-22/5=10 | | -21/29=x+7/29 | | x*4.3=6.8 | | 5k+7k+1-1=3k+9k+5-4 | | 16t^2+79t+5=0 | | 4(2−4y)=8y+36 | | 4x+62=3x-8 | | 3x+25=5x+5 | | 6a^=24 | | z²-4=0 | | x^2=(x+4)(x-2) | | 5(2(x+1)=7x+14 | | 10=8+8b-6b | | 4(9r+6)=32r+2r+8+6 | | -9s+20=-34 | | –40=2y+8y | | 6a+40=a | | x~4.3=6.8 | | 5x-27=2x+51 | | 4(q-65)=44 | | 4y20=100 | | -x+7=(2x+1) | | 0.6y-0.6=0.2-0.9y | | 2+x5=22 |